2003
DOI: 10.1021/es0201348
|View full text |Cite
|
Sign up to set email alerts
|

Relative Potencies and Combination Effects of Steroidal Estrogens in Fish

Abstract: The natural steroids estradiol-17beta (E2) and estrone (E1) and the synthetic steroid ethynylestradiol-17alpha (EE2) have frequently been measured in waters receiving domestic effluents. All of these steroids bind to the estrogen receptor(s) and have been shown to elicit a range of estrogenic responses in fish at environmentally relevant concentrations. At present, however, no relative potency estimates have been derived for either the individual steroidal estrogens or their mixtures in vivo. In this study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
254
2
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(280 citation statements)
references
References 38 publications
20
254
2
4
Order By: Relevance
“…1,46−50 The lowest observed effect level (LOEL) affecting vitellogenin production in juvenile female rainbow trout was found to be as low as 3.3 ng E1/L. 51 Furthermore, the possible impact of hormone exposure on terrestrial organisms has not been documented. However, Kinney et al 52 demonstrated the uptake of wastewater-derived compounds by earthworms and this suggests the potential for bioaccumulation of these compounds in the food web.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…1,46−50 The lowest observed effect level (LOEL) affecting vitellogenin production in juvenile female rainbow trout was found to be as low as 3.3 ng E1/L. 51 Furthermore, the possible impact of hormone exposure on terrestrial organisms has not been documented. However, Kinney et al 52 demonstrated the uptake of wastewater-derived compounds by earthworms and this suggests the potential for bioaccumulation of these compounds in the food web.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Several steroid hormones have been detected in water and sediment samples (Lai et al, 2000;Thorpe et al, 2003). Agricultural and other anthropogenic activities are principal non-point sources for steroid hormones in water and sediment systems (Kolpin et al, 2002).…”
Section: Article In Pressmentioning
confidence: 99%
“…One of the most reported biological effects is fish feminization found in various rivers (Angus et al, 2002;Harries et al, 1997;Jobling et al, 1998;Kristensen et al, 2007;Xie et al, 2010). The observed effects in fish include vitellogenin induction, abnormal development of gonads (Harries et al, 1997;Lye et al, 1997;Jobling et al, 2002) and secondary sexual characteristics (Batty and Lim, 1999;Xie et al, 2010), which have been linked to some estrogenic compounds in the effluents of sewage treatment plants (Harries et al, 1997;Jobling et al, 2002;Lye et al, 1997;Thorpe et al, 2003;Xie et al, 2010). These compounds include 4-t-octylphenol (4-t-OP), 4-nonylphenols (4-NP), bisphenol-A (BPA), estrone (E1), estradiol (E2) and triclosan (TCS), which have been demonstrated to have in vitro and/or in vivo estrogenic activities (Foran et al, 2000;Ishibahsi et al, 2004;Jobling and Sumpter, 1993;Jobling et al, 1995;Raut and Angus, 2010;Stasinakis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%